Bacterial Endophytes Isolated from Plants in Natural Oil Seep Soils with Chronic Hydrocarbon Contamination - Lumactud, Rhea; Shen, Shu Yi; Lau, Mimas; Fulthorpe, Roberta (Frontiers in Microbiology, 2016)
The bacterial endophytic communities of four plants growing abundantly in soils highly contaminated by hydrocarbons were analyzed through culturable and and culture-independent means. Given their tolerance to the high levels of petroleum contamination at our study site, we sought evidence that Achillea millefolium, Solidago canadensis, Trifolium aureum and Dactylis glomerata support high levels of hydrocarbon degrading endophytes. A total of 190 isolates were isolated from four plant species. The isolates were identified by partial 16S rDNA sequence analysis, with class Actinobacteria as the dominant group in all species except Solidago canadensis, which was dominated by Gammaproteobacteria. Microbacterium foliorum and Plantibacter flavus were present in all the plants, with M. foliorum showing predominance in D. glomerata and both endophytic bacterial species dominated T. aureum. More than 50% of the isolates demonstrated degradative capabilities for octanol, toluene, naphthalene, kerosene or motor oil based on sole carbon source growth screens involving the reduction of tetrazolium dye. P. flavus isolates from all the sampled plants showed growth on all the petroleum hydrocarbons substrates tested. Mineralization of toluene and naphthalene was confirmed using gas-chromatography. 16S based terminal restriction fragment length polymorphism analysis revealed significant differences between the endophytic bacterial communities showing them to be plant host specific at this site. To our knowledge, this is the first account of the degradation potential of bacterial endophytes in these commonly occurring pioneer plants that were not previously known as phytoremediating plants.